Evolutionary Multiobjective Optimization with a Segment-Based External Memory Support for the Multiobjective Quadratic Assignment Problem - Unveren, Ahmet; Acan, Adnan (2005 IEEE Congress on Evolutionary Computation, 2005)
[Abstract Not Available]
Keywords: Optimization